Structural Basis for the Thermostability of Sulfur Oxygenase Reductases - 尤晓颜 孟珍 陈栋炜 郭旭 Josef Zeyer 刘双江 姜成英 (Chinese journal of chemical engineering, 2012)
The thermostability of three sulfur oxygenase reductases （SORs） was investigated from thermoacidophilic achaea Acidianus tengchongensis （SORAT） and Sulfolobus tokodaii （SORsT） as well as the moderately thermophilic bacterium Acidithiobacillus sp. SM-1 （SORsB）. The optimal temperatures for catalyzing sulfur oxidation were 80 ℃ （SORAT）, 85 ℃ （SORsT）, and 70 ℃ （SORsB）, respectively. The half-lives of the three SORs at their optimal catalytic conditions were 100 min （SORAT）, 58 min （SORsT）, and 37 min （SORsB）. In order to reveal the structural basis of the thermostability of these SORs, three-dimensional structural models of them were generated by homology modeling using the previously reported high-resolution X-ray structure of SORAA （from Acidianus ambivalens） as a template. The results suggest that thermostability was dependent on： （a） high number of the charged amino acid glutamic acid and the flexible amino acid proline, （b） low number of the therraolabile amino acid glutamine, （c） increased number of ion pairs, （d） decreased ratio of hydrophobie accessible solvent surface area （ASA） to charged ASA, and （e） increased volumes of the cavity. The number of cavities and the number of hydrogen bonds did not signifieantly affect the thermostability of SORs, whereas the cavity volumes increased as the thermal stability increased.